2006
DOI: 10.3390/ijerph2006030006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of UV-B Radiation on Bufo arenarum Embryos Survival and Superoxide Dismutase Activity

Abstract: The exposure of Bufo arenarum embryos to 300–310 nm UV-B at a dose of 4,104 Joule/m2 resulted in 100% lethality within 24 hr while 820 Joule/m2 was the NOEC value for short-term chronic (10 days) exposure. The dose response curves show that lethal effects are proportional with the dose and achieve its highest value within 48 hr post exposure. The superoxide dismutase (SOD) activity in amphibian embryos for sublethal UV-B exposures was evaluated by means of UV-B treatments with 273 (A), 820(B), 1368(C) and 1915… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The assumption that melanin could have a major role against deleterious effects caused by UVB radiation on R. (Bufo) arenarum embryos is in line with the study reported by Perotti and Diéguez [9] in which the photoprotection against UVB radiation in three amphibian species was associated to the melanin content of the embryo. On the other hand, photolyase, one of the principal photo repair enzymes induced by UVB irradiation and antioxidant molecules such as catalase, superoxide dismutase, and glutathion peroxidase, could also contribute to the protection of UVB‐irradiated embryos [15,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption that melanin could have a major role against deleterious effects caused by UVB radiation on R. (Bufo) arenarum embryos is in line with the study reported by Perotti and Diéguez [9] in which the photoprotection against UVB radiation in three amphibian species was associated to the melanin content of the embryo. On the other hand, photolyase, one of the principal photo repair enzymes induced by UVB irradiation and antioxidant molecules such as catalase, superoxide dismutase, and glutathion peroxidase, could also contribute to the protection of UVB‐irradiated embryos [15,32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Rhinella (Bufo) arenarum embryos, it was found that sublethal UVB doses resulted in a rapid but transient increase in superoxide dismutase activity. However, in the case of lethal doses it did not differ significantly from controls, suggesting that the response capacity was defeated [15]. On the other hand, antioxidant agents like selenium and zinc could be beneficial regarding the enhanced survival of UVB radiation–treated amphibian embryos previously exposed to these antioxidants [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the protective screening role of the superficial mucus layer on tadpoles has not been considered, nor is it known if amphibians are able to accumulate screening compounds through their diet. In amphibians, neither antioxidants nor heat shock proteins have been well studied, but in response to UVR exposure, the activity and concentration of the antioxidant, superoxide dismutase, has been shown to increase [70,71], whereas the activity of catalyse does not [72], and the abundance of the heat shock protein, hsp72, increases following heat shock [72]. The DNA repair mechanism of photoreactivation has been examined in numerous amphibian species, but less is known of excision repair.…”
Section: Amphibian Defences Against Uvrmentioning
confidence: 99%
“…In particular, amphibian embryos are useful indicators of environmental pollution and they are employed to assess the embryotoxicity of various chemicals including pyrethroid insecticides [14], solvents [15], metals such as copper [16], flavonoids such as naringenin [17] and different environmental samples, like surface waters, sediments, drinking water, groundwater, industrial effluents, urban runoff and hazardous waste sites [13,18,19]. On the other hand, various studies have focused on the effects of UV-B radiation on embryos survival [20] and photodynamic toxicity [21]. These studies have shown that resistance to environmental agents can change significantly throughout development [15,22].…”
Section: Introductionmentioning
confidence: 99%